Student’s Public Speaking Ability Through Presentation Task - Yuslaili Ningsih; Nanik Mariyati; Nila Susanti (Politeknik Negeri Jember, 2023)
This study attempts to describe the ability of speaking skill as oral communication in public by giving the task of individual presentation performance. This study addresses to the result of speaking course as a part of Intermediate English subject. It was conducted to Renewable Energy Engineering students in the academic year of 2022-2023 as well as their main objective of English Study. The researcher is interested to have the data of public speaking achievement because the importance of public speaking skill regarding inability of students to speak in public or perform oral presentation. When all oral presentations are marked as evidence that students' speaking abilities could meet the needs of the industry, this has become more difficult. Unfortunately, graduates nowadays do not possess the degree of oral presenting abilities that are fulfil the demand of stake holder. In this research, the research study is designed as descriptive quantitative research to have the data of students public speaking ability and describe their performance. The researcher used random sampling and Task based Test instrument to have the data of student public speaking ability and also observation to have the data of student public speaking performance. The research finding would be included of the student performance and the task result by speaking rubric which is included the speaking skill components. The results of research showed that by giving presentation task, it has good level for students’ public speaking ability and the result of presentation task builds the Renewable Energy Engineering student’s confidence to perform public speaking.